A study of fine needle aspiration cytology and histopathology correlation of salivary gland neoplasms in a tertiary care hospital: an observational study - Malik, Asima; Mushtaq, Ahlam; Bhat, Salma; Naik, Suhail (International Journal of Contemporary Pediatrics, 2025)
Background: Salivary gland lesions contribute to 3 to 6.5% of all neck and head neoplasms in adults. The objective of the current study was to determine the frequency and distribution of various salivary gland neoplasms using fine needle aspiration cytology (FNAC), and their histopathological correlation to ascertain the predictive value of FNAC in diagnosing these lesions. Methods: A prospective hospital-based observational study conducted in the department of Pathology, Government Medical College Srinagar from March 2024 to April 2025. All the patients with salivary gland lesions in the age group of 0 to 70 years were enrolled in this study. The FNAC and histopathological examination (HPE) were done in all the swellings of the salivary glands. Results: In our study, salivary gland lesions were more commonly observed in males (53.7%) and predominantly occurred in the 21–60 years age group (30 cases). The parotid gland was the most frequently involved site (60.9%). Benign tumors constituted 56% of cases, followed by non-neoplastic lesions and malignant tumours’, each accounting for 21.95% of cases. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of FNAC with respect to HPE were 83.3%, 94.3%, 71.4%, and 97.1%, respectively. Conclusion: FNAC is a reliable, minimally invasive, and cost-effective diagnostic tool for evaluating salivary gland lesions. It demonstrates high sensitivity and specificity in distinguishing benign from malignant lesions, making it a valuable preliminary diagnostic method. However, histopathological examination remains the gold standard for definitive diagnosis.